Proliferative glomerulonephritis with monoclonal immunoglobulin deposition coexisting with ANCA-associated glomerulonephritis: a case report - Cheng, Yaqian; Zhang, Yifan; Chen, Hui; Zheng, Yiyi; Wang, Zemin (Frontiers in Immunology, 2025)
Proliferative glomerulonephritis with monoclonal immunoglobulin deposition (PGNMID) is a rare variant of monoclonal gammopathy of renal significance (MGRS). Although the pathogenesis of PGNMID is not yet fully understood, it is currently hypothesized to originate from the intraglomerular deposition of pathogenic monoclonal immunoglobulins secreted by B cells or plasma cells. Typically, these deposits exhibit light chain restriction, with κ light chains being the most prevalent. Therapeutic strategies for PGNMID are based on targeting the abnormal or potential clone. However, the combination of corticosteroids and cyclophosphamide has also been reported. In this report, we describe an extremely rare clinical case of λ light chain type PGNMID occurring simultaneously with ANCA-associated glomerulonephritis. After treatment with the combination of corticosteroids and cyclophosphamide, the patient demonstrated reduced proteinuria and stable renal function.